Britain under Brexit (Социология: теория, методы, маркетинг, 2016)
On 8 July 2016, English Conversation Club for Sociologists located at the Institute of Sociology held a round table on the occasion of the United Kingdom's withdrawal from the European Union. Ukrainian sociologists together with their colleagues from University of Bedfordshire and University of Glasgow discussed the EU referendum results and tried to envision how post-Brexit Europe 'would look like.